Rap francophone: création d'identité culturelle « in action » - Szabó-Gilinger, Eszter (Verbum – Analecta Neolatina, 2007)
The present paper studies the cultural and linguistic practices of Francophone (both mother tongue and foreign language speaker) rap groups using their lyrics as data to be analyzed. The methodology chosen is of a double nature: sociolinguistics and critical discourse analysis are used in order to arrive at a more complete picture. The analysis suggests that code-switching is a means through which rappers can create an identity for themselves which identifies them with the African American origins of rap music while allowing for a strong, alternative, national identity. It seems visible that the multilingual identity is one which is gladly embraced because it allows for a wider variety of linguistic practices.